Listing of Ghanaian Power Utilities on the Ghana Stock Exchange - Agyeman, S. O. (University Of Ghana, 2020)
The study sought to investigate whether public trust in Ghana's key power utilities (VRA, GRIDCo & ECG) would be strengthened and whether people would be interested in buying shares if they were to be listed. It also sought to determine whether the board members of the respective power utilities had the requisite expertise and skills to oversee the operations of the companies. A survey was conducted to determine public confidence in listing power utilities on the stock market. Annual reports were used to evaluate the knowledge and skills needed to run these utilities. Guidelines from the Corporate Governance Manual (CGM) for public companies was used to aid in the identification of these skills. According to the results of the survey, 62 % of respondents assert that the listing of power utilities would lead to an increase in the trust of those utilities. 63% also registered their interest in purchasing shares of these utilities should they be floated. These findings are significant at 5% level. An appraisal by the Board of Directors of the three key power utilities from 2009 to 2020 revealed that 96% of them met the skill requirement needed to be board members of Ghana Public Services as set out in the CGM. An analysis of the breakdown of qualifications however reported that the Information and Communication Technology (ICT) category have had low representation over the years. It is imperative that individuals with the requisite expertise are appointed as board members to provide insight into how technology can be leveraged for the efficient and smooth operations of the power utilities. The study shows public credibility and a viable opportunity to raise capital and ensure effective management if the utilities are listed. Keywords and phrases: Board Members, Corporate Governance Manual (CGM), Electricity Company of Ghana Limited (ECG), Ghana Grid Company Limited (GRIDCo), Ghana Stock Exchange (GSE), Volta River Authority (VRA).
MBA. Finance
Keywords: Ghana Stock Exchange (GSE); Volta River Authority (VRA); Ghana Grid Company Limited (GRIDCo); Electricity Company of Ghana Limited (ECG); Power Utilities